Marine protected areas, spatial scales, and governance: implications for the conservation of breeding seabirds - Yorio, Pablo Martin (2009)
As in many regions worldwide, seabird colonies in Argentina are important conservation targets of marine protected areas (MPAs). Seabirds are wide ranging, often crossing jurisdictional boundaries during foraging. Using a recently designated MPA as a case study, this article discusses the challenges of protecting breeding seabirds given their spatial requirements and use of different jurisdictions. Seabirds breeding at the MPA have distinct foraging strategies. Rock Shags and Olrog's Gulls forage inshore within the MPA. Imperial Cormorants, Magellanic Penguins, and Southern Giant Petrels, in contrast, often feed beyond the MPA's jurisdiction, traveling into provincial, federal, or international waters where they can be affected by fisheries and oil development. This indicates the need of management actions beyond MPA boundaries. The large scale and connectivity of marine ecosystems and the variety of economic pressures require the participation of stakeholders and several government agencies in conservation issues, and thus integrated coastal management and marine spatial planning appear as options to complement the use of MPAs. Although MPAs are a valuable tool to conserve breeding seabirds, increased efforts are needed to design new governance structures and complementary strategies for spatial protection so as to deal with the biological, social, and political complexities of marine systems.